Respiratory magnetic resonance imaging biomarkers in Duchenne muscular dystrophy. Issue 9 (28th July 2017) - Mankodi, Ami; Kovacs, William; Norato, Gina; Hsieh, Nathan; Bandettini, W. Patricia; Bishop, Courtney A.; Shimellis, Hirity; Newbould, Rexford D.; Kim, Eunhee; Fischbeck, Kenneth H.; Arai, Andrew E.; Yao, Jianhua
Abstract: Objective: To examine the diaphragm and chest wall dynamics with cine breathing magnetic resonance imaging (MRI) in ambulatory boys with Duchenne muscular dystrophy (DMD) without respiratory symptoms and controls. Methods: In 11 DMD boys and 15 controls, cine MRI of maximal breathing was recorded for 10 sec. The lung segmentations were done by an automated pipeline based on a Holistically‐Nested Network model (HNN method). Lung areas, diaphragm, and chest wall motion were measured throughout the breathing cycle. Results: The HNN method reliably identified the contours of the lung and the diaphragm in every frame of each dataset (~180 frames) within seconds. The lung areas at maximal inspiration and expiration were reduced in DMD patients relative to controls ( P  =   0.02 and <0.01, respectively). The change in the lung area between inspiration and expiration correlated with percent predicted forced vital capacity (FVC) in patients ( r s  = 0.75, P  =   0.03) and was not significantly different between groups. The diaphragm position, length, contractility, and motion were not significantly different between groups. Chest wall motion was reduced in patients compared to controls ( P  <   0.01). Interpretation: Cine breathing MRI allows independent and reliable assessment of the diaphragm and chest wall dynamics during the breathing cycle in DMD patients and controls. The MRI data indicate that ambulatory DMD patients breathe at lower lung volumes than controls when their FVC is in the normal range. The diaphragm moves normally, whereas chest wall motion is reduced in these boys with DMD.